Case Report: Let Us Not Forget the Treatment That Some Patients Have Received—The Brief 50-Year History of a Kidney Transplant Survivor - Nordheim, Espen; Raki, Melinda; Midtvedt, Karsten (Frontiers in Medicine, 2022)
Background The medical progress following solid organ transplantation from the early 1960s-70s and until today has been enormous. Some patients we meet in the clinic have “lived through” this progress and have histories to tell that one must not forget. This is the brief history of a “transplant survivor”. Case presentation In 1970 a young women developed acute oedema, proteinuria, hypertension and oliguria during pregnancy. The delivery was induced as an emergency procedure, but neither the child nor the kidney function could be saved. She started dialyses and received a kidney transplant four years later from her father (then 55 years of age). The immunosuppression consisted of steroids and azathioprine which was maintained until 2011, when azathioprine was switched to everolimus due to skin cansers. Before this, our patient felt confidence in and safe on prednisolon/azathioprine. Retrospectively, the avoidance of calcineurin inhibitors might have been beneficial for this patient who has preserved an excellent renal function with s-creatinine levels around 100 µmol/l and just had sparse fibrosis detected in a recently performed graft biopsy. The kidney graft is now 101 year old and is still working 24/7. Conclusions Our patient received a kidney transplant for 46 years ago and still has a remarkable stable graft function and s- creatinine levels around 100 µmol/l. This case report illustrates the potential endurance of the kidneys and is a reminder to keep taking individualized treatment decisions even though new treatment alternatives promise superiority.